Smart Media, Smart Politics: How AI is Reshaping Political Communication and Public Policy - Zhou Beihao (Environment and Social Psychology, 2026)
This study examines citizens’ perceptions of Artificial Intelligence (AI) in political communication through a qualitative research design based on semi-structured interviews with 40 purposively selected participants. Responses were gathered through semi-structured interviews and then processed within a framework utilizing Python where various filters were applied including token frequency counts; co-occurrence mapping and sentiment polarity scores to analyze the data. A number of common themes emerged from the data; most significantly the most discussed theme was Awareness, with 37 of the 40 individuals referring to this. All 40 individuals referred to the themes of Trust, Ethics, and Behaviour; however, the theme of ethics was the most highly coded with 234 occurrences. Respondents reported that they tended to have a trust that was cautious of the AI generated political information, and provided examples of how there was a lack of transparency, presence of bias, manipulation of information and the potential for misinformation. While it was determined within the analysis that AI will not have a large impact on changing opinions about political stakeholders, it was also noted that the information produced by AI impacts visibility, prioritization and engagement with political information. Overall, the results suggest a duality of intent seen amongst respondents; they see AI as a potential Information Tool but also as an Ethical and Credibility Challenge. The need for citizen center governance of AI is stressed in the conclusions provided.